Spatial transcriptomics reveals altered lipid metabolism and inflammation-related gene expression of sebaceous glands in psoriasis and atopic dermatitis - Seiringer, Peter; Hillig, Christina; Schäbitz, Alexander; Jargosch, Manja; Pilz, Anna Caroline; Eyerich, Stefanie; Szegedi, Andrea; Sochorová, Michaela; Gruber, Florian; Zouboulis, Christos C.; Biedermann, Tilo; Menden, Michael P.; et al. (Frontiers in Immunology, 2024)
Sebaceous glands drive acne, however, their role in other inflammatory skin diseases remains unclear. To shed light on their potential contribution to disease development, we investigated the spatial transcriptome of sebaceous glands in psoriasis and atopic dermatitis patients across lesional and non-lesional human skin samples. Both atopic dermatitis and psoriasis sebaceous glands expressed genes encoding key proteins for lipid metabolism and transport such as ALOX15B, APOC1, FABP7, FADS1/2, FASN, PPARG, and RARRES1. Also, inflammationrelated SAA1 was identified as a common spatially variable gene. In atopic dermatitis, genes mainly related to lipid metabolism (e.g. ACAD8, FADS6, or EBP) as well as disease-specific genes, i.e., Th2 inflammation-related lipid-regulating HSD3B1 were differentially expressed.On the contrary, in psoriasis, more inflammation-related spatially variable genes (e.g. SERPINF1, FKBP5, IFIT1/3, DDX58) were identified. Other psoriasis-specific enriched pathways included lipid metabolism (e.g. ACOT4, S1PR3), keratinization (e.g. LCE5A, KRT5/7/16), neutrophil degranulation, and antimicrobial peptides (e.g. LTF, DEFB4A, S100A7-9). In conclusion, our results show that sebaceous glands contribute to skin homeostasis with a cell type-specific lipid metabolism, which is influenced by the inflammatory microenvironment. These findings further support that sebaceous glands are not bystanders in inflammatory skin diseases, but can actively and differentially modulate inflammation in a disease-specific manner.